Taxonomy and phylogeny of a new Central American beetle genus: Catrachia (Coleoptera: Scarabaeidae) - Coca-Abia, María Milagro (2006)
A new genus and two species of Melolonthinae from Honduras and Nicaragua are described. A phylogenetic analysis, carried out using morphological characters, suggests that Catrachia is a strongly sup-ported monophyletic group. Catrachia is therefore established as a new genus, constituted by two new species, Catrachia mariana and Catrachia nica.